2009
DOI: 10.1016/j.oraloncology.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic ameloblastoma – A review

Abstract: SUMMARY Among the ameloblastomas, the desmoplastic variation is rare. The desmoplastic ameloblastoma (DA) is characterized by specific clinical, imaging, and histological features. The here presented retrospective analysis investigated the clinicoradiographic features of an overall of 115 DA-cases, having been reported in literature from 1984 to 2008. DA showed a nearly equal male to female ratio (55/59) with a prevalence within the forth and fifth decades. Sixty-two lesions occurred in the mandible and fifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 35 publications
4
69
0
11
Order By: Relevance
“…[30][31][32][33][34] However, the well-defined periphery of ameloblastoma is commonly uniformly thin and corticated, unlike the findings of this review of IMC and the case reported by Raut and Khedkar, 22 of an uneven, thick, sclerotic a b Figure 1 (a) Axial and (b) coronal. CT bone windows of Case 1 show the epicentre of the lesion at the root apex in the right maxillary alveolar process.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…[30][31][32][33][34] However, the well-defined periphery of ameloblastoma is commonly uniformly thin and corticated, unlike the findings of this review of IMC and the case reported by Raut and Khedkar, 22 of an uneven, thick, sclerotic a b Figure 1 (a) Axial and (b) coronal. CT bone windows of Case 1 show the epicentre of the lesion at the root apex in the right maxillary alveolar process.…”
Section: Resultsmentioning
confidence: 91%
“…Another consistent radiographic feature of IMC in this study, also noted in the case series by Johnson and Velez, 16 is the presence of internal foci of amorphous sclerotic bone, a finding not typical of solid, multicystic ameloblastoma. [30][31][32][33][34] However, the desmoplastic variant of ameloblastoma and cases of recurrent conventional ameloblastoma have been documented to contain a similar radiographic internal structure to IMC, 30,34 and may prove difficult, if not impossible, to distinguish from IMC ( Figure 5). The typical behaviour of the IMC seen in this review is to break through the outer cortex of the jaw and extend into surrounding soft tissue.…”
Section: Resultsmentioning
confidence: 99%
“…However, a well-defined radiolucent lesion may occur in a similar manner to that reported by Reichart et al (11), where 51% of the tumors were described as unilocular. Nevertheless, the DA frequently appears as a poorly defined, mixed, radiolucent-radiopaque lesion mimicking a benign fibro-osseous lesion, especially when evaluating panoramic and periapical radiographs (2,7,12). Through the CBCT, however, it is possible to verify the tomographic limits of the DA.…”
Section: Case Reportmentioning
confidence: 99%
“…DA is a tumor with specific clinical, image, and histological features. In additional, DA is a rare form of tumor and has been described in 115 cases in English literature (2). Radiographically, 50% of DA shows an image suggesting a benign fibro-osseous lesion (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation